The Gander Lake and Davidsville Groups of Northeastern Newfoundland: New Data and Geotectonic Implications - Kennedy, M. J.; McGonigal, M. H. (Canadian Journal of Earth Sciences, 1972)
Structural studies of rocks in the Gander region of Newfoundland and on the coast to the north have indicated that rocks that were previously assigned to the Middle Ordovician Gander Lake Group actually consist of a composite sequence that contains pre-Middle Ordovician polyphase deformed metasedimentary rocks and even older gneissic rocks as well as Middle Ordovician sediments and mafic volcanics. The possible implications of these results are discussed and map units in the region are redefined.